Along or across the visual axis: a comparison of two ultrasound screen, needle and transducer orientation techniques. (January 2021) - Di Franco, Chiara; Tayari, Hamaseh; Nardi, Samanta; Briganti, Angela
Abstract: Objective: To evaluate two transducer and needle handling methods, along the visual axis (AL) and across the visual axis (AC), in non-skilled and skilled clinicians. Study design: Prospective randomized crossover study. Method: A total of 26 students with no ultrasound locoregional anaesthesia experience (non-skilled group) and six clinicians experienced and familiar with ultrasound locoregional anaesthesia (skilled group) were enrolled. The non-skilled group was asked to perform two tasks: the first on a phantom and the second on canine cadavers, whilst the skilled group performed only the second task. The tasks consisted of guiding the tip of the needle to a target point (simulated nerve on the jelly phantom and sciatic nerve on the cadavers) using two different methods of needle handling—AL or AC. All operators performed each task three times for each method. The time to drive the needle to the target for the two methods was analysed with a paired Student t test, and the number of times the needle was not visualized on the screen between the groups was compared using an unpaired Student t test. Data are presented as mean ± standard deviation. Value of p < 0.05 was considered significant. Results: The AL method, compared with the AC method, resulted in shorter performance time in both skilled (9 ± 5 versus 20 ± 8 seconds for the second task) and non-skilled groups (9 ± 8 versus 17 ± 15 seconds for the first task and 18 ± 11 versus 32 ± 26 seconds for the second task). Conclusion and clinical relevance: In both groups, the AL method significantly reduced the time to complete the task. Results from this study indicate that the AL method should be the preferred method for learning/teaching ultrasound-guided regional anaesthesia.